Ensaios em board interlocking - Barros, Thiago de Sousa (2017)
Governance has become a relevant topic within the corporate context in recent years, largely because of the proliferation of multinational companies, the development of capital markets and the growing number of investors. In this scenario, company Boards of Directors, which are central figures when it comes to complying with monitoring functions, exercising good governance practices and protecting shareholders, have been the object of study in both the business environment and the academic sphere. The shape, profile and independence of the Board of Directors can affect the decisions that companies take, especially with regard to financial investment issues. Such aspects can also have an impact on company performance and enable firms to have greater or lesser access to information and resources. The aim of this thesis, therefore, is to investigate board interlocking, a situation in which a director has a seat on the boards of more than one company, a characteristic normally seen in global markets. Some of the empirical evidence in contemporary financial literature, however, is antagonistic as far as concerns the real benefits and losses arising from the use of this strategy of having interconnected Boards of Directors, either by way of shared directors, or political interlocking. In view of these discrepant results and to comply with the research objectives that were outlined, three tests were developed and form part of this work. The first one, using a sample of 153 Brazilian companies for the 2000-2015 series, associates board interlocking with mergers and acquisitions, since this can be a way of reducing information asymmetry and collection costs, thus affecting participation in M&As. Small World formations may occur within a network of companies; these are groups in which information circulates even faster among members. The second test, therefore, involved a sample of 174 Brazilian firms and investigated the existence of these Small Worlds in the network of Brazilian firms, considering the period 2000-2015, and the influence of these Small Worlds on merger and acquisition processes. Finally, the third test, based on a sample of Brazilian companies and considering the last four presidential elections in Brazil (2002, 2006, 2010 and 2014), focused on the relationship between political interlocking, as measured by election campaign donations and directors with a political background, and the forecasts of analysts, using as a proxy the implicit cost of capital. The results of the first test suggest that firms with a higher degree, in other words, companies that have a greater number of ties with others by way of interconnected boards are more likely to become involved in mergers and acquisitions. The second test makes it possible to infer that Small Worlds are formed in annual company networks, given the high clustering coefficient and small average distance between firms. Taking into consideration both Brazilian and international mergers and acquisitions, the results, however, indicate that a Small World does not have a significant effect on the carrying out of M&As. Finally, the third test shows that donations to electoral campaigns in the Brazilian context can generate negative effects. Market analysts consider that there is greater risk with this type of political interlocking, which consequently leads to a higher implied cost of capital for the companies. On the other hand, having board members with a political background did not prove to have a significant relationship, except during the fiscal crisis period (as measured by the negative GDP dummy and which included the 2014-2015 hiatus) when analysts 'priced' political background as being a negative factor, thus raising the implicit cost of capital.